The Formation, Structure and Activity of Phytochemicals 2015
DOI: 10.1007/978-3-319-20397-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Containing Constituents of Black Cohosh: Chemistry, Structure Elucidation, and Biological Activities

Abstract: The roots/rhizomes of black cohosh (Actaea racemosa L. syn. Cimicifuga racemosa [L]. Nutt., Ranunculaceae) have been used traditionally by Native Americans to treat colds, rheumatism, and a variety of conditions related to women’s health. In recent years black cohosh preparations have become popular dietary supplements among women seeking alternative treatments for menopausal complaints. The popularity of the plant has led to extensive phytochemical and biological investigations, including several clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…A limitation of the current study is the inability to directly relate the amounts of the chemical markers shown in Figure 1 to the potencies of the cohosh samples shown in Figure 4, as it is not known whether dissolving the extracts and powders in DMSO may have differentially affected the solubility of these various chemical markers in culture medium. Furthermore, a correlative analysis of each of the 13 chemical markers identified in our samples with potencies in the MN assay may be uninformative, as more than 100 constituents have been reported to be present in BCEs [Nikolic et al, 2015; Wang et al, 2011], and the possibility remains that an unknown but active constituent could co-vary with a known, but inactive, constituent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A limitation of the current study is the inability to directly relate the amounts of the chemical markers shown in Figure 1 to the potencies of the cohosh samples shown in Figure 4, as it is not known whether dissolving the extracts and powders in DMSO may have differentially affected the solubility of these various chemical markers in culture medium. Furthermore, a correlative analysis of each of the 13 chemical markers identified in our samples with potencies in the MN assay may be uninformative, as more than 100 constituents have been reported to be present in BCEs [Nikolic et al, 2015; Wang et al, 2011], and the possibility remains that an unknown but active constituent could co-vary with a known, but inactive, constituent.…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine was originally extracted from the corms of Colchicum autumnale (autumn crocus), and has also been extracted from the tuber portion of Gloriosa superba L. (climbing lily), another member of the Colchincaceae family. To date, the Ranunculaceae family of plants, to which Actaea plants belong, has been identified as one of the top three producers of alkaloid compounds [Cordell et al, 2001], and a variety of alkaloids have been identified in black cohosh extracts [Nikolic et al, 2015]. It may be possible that roots from cohosh plants contain colchicine or a similar compound that could both disrupt uptake of cobalamin and induce micronuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that its main function in plants is to strengthen the cell walls and therefore prevent the entry of pathogens into suberizing tissue. The biosynthesis of hydroxycinnamoyl amides has been well studied, but a UGT capable of glucosylating phytoalexins has not been reported to date, although glucosides of the amides have been frequently found (Yahagi et al ., ; Bolleddula et al ., ; Nikolić et al ., , ; Yang et al ., ; Yim et al ., ; Zhang et al ., ; Pei et al ., ; Geng et al ., ; Oliveira de Silva and Batista, ; Wang et al ., ). The biological function of glucosides of hydroxycinnamoyl amides is unclear but they might play a similar role like monolignol glucosides in plant defence (Le Roy et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Cimicifuga , which is rich in medical plants, has confirmed its special curative effect by long‐term use in folk medicine . Among them, one which got a mention is Actaea racemosa L. (Black cohosh), the extract of which has been used for menopausal symptoms and anti‐depression . It is one of the dietary supplements that is currently under evaluation by the Office of Dietary Supplement, National Institute of Health.…”
Section: Introductionmentioning
confidence: 99%